Strategies to serve or receive the service in volleyball - Lee, K. T.; Chin, S. T. (Mathematical Methods of Operations Research, 2004)
We analyze the problem facing the team that wins the toss at the deciding fifth set of a volleyball match. The teams decision to serve or to receive the service can make a difference to the eventual outcome of the match. We characterize the conditions under which it is better to serve or to receive the service at that set. These conditions are obtained by first expressing the exact probability of winning a set in volleyball in terms of the Legendre polynomials.